Ab-initio study of L-Tartaric Acid (LTA) single crystal for NLO application. (November 2015) - Hasmuddin, Mohd.; Abdullah, M.M.; Singh, Preeti; Shkir, Mohd.; Vijayan, N.; Wahab, M.A
Abstract: Single crystals of LTA were grown by slow evaporation solution technique (SEST). Powder X-ray diffractometry (PXRD) confirmed the monoclinic crystal structure, whereas the high resolution X-ray diffractometry (HRXRD) ascertained the good crystalline perfection (FWHM=25 arcsec) of the as-grown single crystal. Optical study demonstrated the high optical transparency (85%). Photoluminescence (PL) spectroscopy illustrated the PL-emission at λ =388 nm and optical band gap 3.2 eV. The SHG efficiency of LTA single crystal (6.61) is comparatively greater than the referenced (KDP) single crystal (6.08). Thermal analysis revealed that the crystal is thermally stable up to 170 °C. The calculated value of the activation energy (Δ E ) and corrected hardness ( H 0 ) for the crystal were found to be equal to 1.16 eV and 46.66 kg/mm 2, respectively. The as-grown LTA single crystals can be used as a potential candidate for NLO material as well as in electronic and optoelectronic devices. Highlights: A single crystal of good crystalline perfection (FWHM=25 arcsec). Comparatively higher SHG efficiency (6.61) confirms good NLO properties. Electrically, thermally and mechanically efficient for NLO devices.